Os dilemas da inclusão de minorias no parlamento brasileiro: a atuação das frentes parlamentares e bancadas temáticas no Congresso Nacional. - Marina Brito Pinheiro (2010)
This work aims to discuss the issue of the political inclusion of minorities and the difficulties of its relationship with the liberal model of representation. Taking into account the literature that discusses the issues related to the exclusionary character of the liberal representation, we discuss some ways of mitigating the effects of this kind of exclusionary representation. Considering this context as a background, we ask about the possibilities of parliamentary groups, commonly known as Bancadas or Frentes Parlamentares, which act in the Brazilian National Congress, do or do not collaborate to ensure the presence of the claims of marginalized groups in society in the parliamentary agenda. As a result we present a set of factors, which when linked, positively or negatively affect the success of these groups bring to the legislative the demands of these groups.